Impact of different dexamethasone treatment protocols in goats for preterm neonatal outcomes - Narciso, Luis Gustavo [UNESP]; Alcindo, Jefferson Filgueira; Bovino, Fernanda; Trevizan, Juliane Teramachi; da Silva Vieira, Dielson [UNESP]; Martins de Almeida, Breno Fernando; Feitosa, Francisco Leydson Formiga [UNESP] (Elsevier, 2022)
This study aimed to evaluate metabolic parameters, such as hemogasometric, glycemic, and lactate values of premature newborns from goats subjected to prenatal dexamethasone treatment using different protocols in comparison with those obtained with previous protocols and studies. The protocols were as follows: Group I received 20 mg dexamethasone at 139 days of gestation; Group II received 2 mg dexamethasone from the 133rd to the 136th day of gestation, 4 mg from the 137th to the 139th day, and 20 mg on the 140th day; Group III received 16 mg dexamethasone from the 139th day, with repeated doses every 12 h until elective surgery; and Group IV received 4, 8, 16, and 20 mg dexamethasone on days 137th, 138th, 139th and 140th days of gestation, respectively. The groups whose mothers received 4, 8, 16, and 20 mg dexamethasone at 137, 138, 139, and 140 days of gestation had higher bicarbonate values at 0, 1, and 48 h compared to the other groups. The highest lactate values were observed at birth, with a gradual reduction in all groups. In all groups, there was an increase in glucose levels after birth, with the highest values observed 48 h after birth. The use of antenatal dexamethasone in goats promotes fetal development, and consequently, lung maturation. More extended protocols seem more efficient, resulting in lower mortality rates and less intense metabolic changes. This study will help establish protocols to overcome the mortality and morbidity associated with preterm ruminants.
Keywords: Caprine; Dexamethasone; Early parturition; Induced parturition